Мас-спектральне дослідження поведінки [1,2,4]триазино[2.3-с]хіназолінів під дією електронного удару - Воскобойнік, Олексій Юрійович; Карпенко, О. В.; Берест, Галина Григорівна; Скорина, Дмитро Юрійович; Носуленко, Інна Степанівна; Коваленко, Сергій Іванович; Коломоєць, Олександра Сергіївна; Воскобойник, А. Ю.; Карпенко, А. В.; Носуленко, И. С.; Коваленко, С. И.; Коломоец, А. С.; et al. (My University, 2013)
Досліджено мас-спектрометричні характеристики ряду 3-R1-6-R2-[1,2,4]триазино[2.3-с]хіназолінон-2-онів, встановлено основні напрямки фрагментації в залежності від характеру замісників. Встановлено, що у всіх сполук зазначеного класу під дією електронного удару відбувається розрив зв’язків С(2)–С(3) та N(3)–N(4) з утворенням характеристичних іонів. Исследованы масс-спектрометрические характеристики ряда 3-R1-6-R2-[1,2,4]триазино[2.3-с]хиназолинон-2-онов, установлены основные направления фрагментации в зависимости от характеразаместителей. Установлено, что у всех соединений указанного класса под действием электронногоудара происходит разрыв связей С(2)-С(3) и N(3)-N(4) с образованием характеристических ионов. During the last decade, the series of articles dedicated to the formation of [1,2,4]triazino[2.3-c]quinazoline system as result of [4+2] - and [5+1]- cyclocondensation were published. Also in the series of publications indicated that the compounds of mentioned class reveals antioxidant, anticancer, antimicrobial and cytotoxic effects and are promising object of research aimed to the creation of new highly efficient drugs. In respect the mentioned above facts development of analytical methods in particular mass-spectrometery, which would allow identification of the above class of compounds is of considerable practical interest. Thus, presented work dedicated to investigation of mass-spectra of [1,2,4]triazino[2.3-с]quinazoline series, analyzing and systematization of obtained data. As objects of study we used a series of 3-R-6-R1-[1,2,4]triazino[2.3-c]quinazoline-2-ones, which were obtained by the described synthetic protocols. The results of mass spectral (EI) study of 3-R-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones showed low intensity of the molecular ion(4.7% - 8.4%). The main direction of fragmentation is cleavage of the C(2)-C(3) and N(3)-N(4) bonds, which yielded stable [1,3]diazeto [1,2-c] quinazolin-2-one cation with peak intensity of 100 % and m/z value 171. Signals of ions with m/z less than 171 mainly caused by the fragmentation of described above cation. A similar fragmentation was observed for of 3-[2-(4-R1)-2-oxoethyl]-2H-[1,2,4]triazino-[2,3-c]quinazolin-2-ones, but the principle difference for this case is the presence of highly intense signals due to cleavage of bonds in the substituent in position 3. For example, in the mass-spectrum of 3-[2-(4-fluorophenyl)-2-oxoethyl]-2H-[1,2,4]triazino-[2,3-c]quinazolin-2-one observed moderately intense signals of cation which was formed as a result of elimination of 4-fluorophenyl fragment (m/z 238) with following separation of CH2CO fragment (m/z 197). Introduction of alkyl or aryl substituent in position 6 of [1,2,4]triazino[2,3-c]quinazolin-2-ones system does not affect the main direction of fragmentation , as in previous cases, there is a cleavage of the C(2)-C(3) and N(3)-N(4) bonds which leads to the ions with m/z 185 and 247 respectively. Among the features of the mass-spectra of mentioned series should be noted significantly higher stability of 2-phenylquinazoline ion cation with m/z value 205 and intensity 78.5% compared to 2-methylquinazoline (m/z 144 , 5.5 %). Mass-spectrum of 3-phenyl-2H-[1,2,4]triazino[2,3-c]quinazolin-2,6-(7H)-dione also characterized by low intensity peak of the molecular ion. Ion peak with m/z 187, which has the highest intensity in the spectrum caused by elimination of benzonitrile fragment. Investigation of 3-R-6-thioxo-6,7-dihydro-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones mass spectra showed that their fragmentation under electron impact differs from the classical for heteroaromatic sulfides [12]. The first step as in the previous cases, there is a cleavage of the C(2)-C(3) and N(3)-N(4), following by emission of low moleculae fragments. The alkylation products of compounds such as 2-((3-R1-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio)acetic acid is similar to the initial thions. High intense signals caused by the elimination of CO2 , COOH and SCH2COOH particles and formation of fragmentary ions with m/z 217 (100 %-75.1%), m/z 216 (88.8% -20.0%) and m/z 171 (100% -48.6 % ) (3-R-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)carboxylic acids under electron impact undergoing described above primary cleavage. The following stages of fragmentation caused by decarboxylation and step-by-step fragmentation of the alkyl moiety. We concluded that substituted 3-R-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones independently of the nature of the substituent have common initial stages of fragmentation, which is consistent with the features of the electronic structure of this heterocyclic system. The main direction of the fragmentation caused by the cleavage of the C(2)-C(3) and N(3)-N(4) bonds. Further fragmentation depends on the nature of substituents and may be used for identification of compounds of this class.
Масс-спектральное исследование поведения [1,2,4]триазино[2.3-с]хиназолинов под действием электронного удара
Mass-spectral study of [1,2,4]triazino[2.3-с]quinazoline series
Keywords: [1,2,4]триазино[2.3-с]хіназоліни; мас-спектрометрія.; [1,2,4]триазино[2.3-с]хиназолины; масс-спектрометрия